ANALISIS KEMAMPUAN KONEKSI MATEMATIK SISWA SMP PADA MATERI BANGUN RUANG SISI DATAR - Lutfia Nursaniah; Nurhaqiqi Nurhaqiqi; Devi Nurul Yuspriyati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study describes the ability of mathematical connections. This study is a qualitative descriptive research with the subject of research as many as 27 students of class IX SMP Negeri 01 Cipongkor West Bandung regency. Subject given a written test in the form of an instrument about the connection consisting of eight items. After that, researchers conducted interviews with selected subjects. From the result of student completion and interview, it is found that the level of mathematical connection ability of junior high school students is still low. This is seen from the mistakes that students do in solving the problem, where students actually already understand the problem quite well as can mention the elements that are known and asked. However, students are less conscientious about how the relationship between the data is known and what is asked. So that students are wrong in choosing the right strategy in the settlement. In addition, this is also influenced by students' lack of understanding in the application of formulas. The errors are caused by several factors, including students are less understanding of the material and students are not able to transform the issues submitted into the knowledge it has.